Nutrition knowledge, attitudes toward physical activity and malnutrition as predictors of social appearance anxiety: a structural equation modeling approach - Turhan, Fatih Harun; İnce, Uğur; Özkeskin, Mehmet; Kayışoğlu, Numan Bahadır; Öztürk, Mehmet Ali; Doğan, Nur Elvan Koç; Kızıltaş, Musa; Karagöz, Berkay; Doğan, İsa (Frontiers in Nutrition, 2025)
BackgroundSocial appearance anxiety (SAA) has emerged as a critical psychosocial concern among young adults, influenced by various behavioral and cognitive factors. Despite growing recognition of the role of health literacy, limited research has examined how nutrition knowledge may influence SAA through indirect pathways.ObjectiveThis study aimed to examine the predictive role of nutrition knowledge on social appearance anxiety, with a particular focus on the mediating effects of physical activity attitudes and malnutrition.MethodsA cross-sectional design with a convenience sample of 338 university-level athletes (Mage = 22.04, SD = 3.46) was employed. Participants completed validated measures of nutrition knowledge, attitudes toward physical activity, malnutrition, and SAA. Structural Equation Modeling (SEM) was used to analyze direct and indirect pathways. Model fit indices and bootstrapping methods were used to test mediation effects.ResultsNutrition knowledge was negatively associated with SAA (β = −0.19, p < 0.001). However, this direct relationship lost significance when physical activity attitudes and malnutrition were introduced as parallel mediators. Mediation analysis revealed significant indirect effects of nutrition knowledge on SAA through both physical activity attitudes (β = −0.30, p < 0.001) and malnutrition (β = −0.42, p < 0.001), supporting a full mediation model. The final model explained 27% of the variance in social appearance anxiety and demonstrated satisfactory fit indices (e.g., RMSEA = 0.065; CFI = 0.93).ConclusionThe findings underscore the importance of targeting both behavioral (physical activity) and physiological (malnutrition) mediators when addressing the impact of nutrition knowledge on social appearance anxiety. Interventions designed to reduce SAA should incorporate components that enhance nutritional literacy and promote positive lifestyle behaviors to improve mental and physical well-being among young adults.